Around the World in Eighty Days - Verne, Jules, 1828-1905 (Lahore Reading Publishing, 2016)
The ultimate adventure story of its time, Jules Verne's most celebrated work follows Phileas Fogg as he attempts to win a wager by traveling around the world in 80 days
Keywords: Voyages around the world -- Wagers -- Adventure stories